Commonly-used antihypertensives and lower urinary tract symptoms: Results from the Boston Area Community Health (BACH) Survey - Hall, Susan A. (2011)
OBJECTIVE: To examine differences in the prevalence of lower urinary tract symptom (LUTS) among users of five common antihypertensive (AHT) classes compared to non-users, adjusted for LUTS risk factors in a large, representative sample. SUBJECTS AND METHODS: Data were from the Boston Area Community Health Survey, a population-based study of community-dwelling male and female (30–79y) residents of Boston, MA for whom prescription drug information was collected (2002–2005). The urologic symptoms of storage, voiding, and nocturia were assessed using interviewer-administered questionnaires and the American Urologic Association Symptom Index. This analysis was conducted among 1,865 participants with an AHT indication. Associations of angiotensin-converting enzyme inhibitors, beta blockers, calcium channel blockers (CCBs), loop and thiazide diuretics with the three groups of LUTS were estimated using odds ratios (ORs) and 95% confidence intervals (CIs) from multivariate logistic regression (referent group=untreated hypertension). Overlap in use was accounted for using monotherapy and combination therapy exposure categories. RESULTS: Among women, monotherapy with CCBs was associated with increased prevalence of nocturia (OR=2.65, 95% CI: 1.04–6.74) and voiding symptoms (OR=3.84, 95% CI: 1.24–11.87); these results were confined to women aged <55. Among men of all ages, positive associations were observed for thiazides and voiding symptoms (monotherapy OR=2.90, 95% CI: 1.17–7.19), and loop diuretics and nocturia (combination therapy OR=2.55, 95% CI: 1.26–5.14). CONCLUSION: Results are consistent with the hypothesis that certain AHTs may aggravate LUTS. The presence of new or worsening LUTS among AHT users suggests review of medications and consideration of a change in AHT class.